Comparison of Mini Nutritional Assessment- Short Form (MNA-SF) versus Mini Nutritional Assessment- Long form (MNA-LF) in older trauma Patients - Purucker, Katja; Schrader, Eva; Goisser, Sabine; Sieber, Cornel; Volkert, Dorothee; Singler, Katrin (Zeitschrift für Gerontologie und Geriatrie, 2013)

Dietary assessment methods for older persons: what is the best approach? - Volkert, Dorothee; Schrader, Eva (Current Opinion in Clinical Nutrition and Metabolic Care, 2013)
Purpose of reviewDue to the present worldwide demographic change and the close relation between nutrition and health up to old age, accurate dietary assessment in older persons gains in interest and importance. The purpose of this article is to give an overview of dietary assessment methods for this growing population group, with emphasis on recent findings, and to highlight future research needs.Recent findingsKnowledge on dietary assessment in older and especially in very old persons is limited and specific aspects were selectively examined in recent times. For use in epidemiological studies, short food frequency questionnaires were developed and validated, which seem to be promising to reduce the burden for respondents and interviewers. In the clinical setting estimation of dietary intake by plate diagrams was shown to be valid, and in different populations anorexia emerged as an important prognostic parameter.SummaryThe best approach for dietary assessment in older persons depends on the purpose of the assessment and the specific abilities and impairments of the sample or person under study. Research is needed to further develop existing methods in order to meet the needs of old and very old persons and to identify major modifiable prognostic nutritional characteristics.
Keywords: anorexia of aging; dietary assessment; elderly; screening for malnutrition

Low postoperative dietary intake is associated with worse functional course in geriatric patients up to 6 months after hip fracture - Goisser, Sabine; Schrader, Eva; Singler, Katrin; Bertsch, Thomas; Gefeller, Olaf; Biber, Roland; Bail, Hermann-Josef; Sieber, Cornel; Volkert, Dorothee (British Journal of Nutrition, 2015)
We examined the relationship between postoperative dietary intake (DI) of geriatric hip fracture (HF) patients and their functional and clinical course until 6 months after hospital discharge. In eighty-eight HF patients >= 75 years, postoperative DI was estimated with plate diagrams of main meals over four postoperative days. DI was stratified as >50, >25-50, <= 25 % of meals served. Functional status according to Barthel index (activities of daily living) and patients' mobility level before fracture, postoperatively, at discharge and 6 months later were assessed and related to DI levels. In-hospital complications were recorded according to clinical diagnosis. Associations were evaluated using ?2 and Kruskal-Wallis tests, and repeated-measures ANOVA and ANCOVA. Postoperatively, 28 % of participants ate >50 %, 43 % ate >25-50 % and 28 % <= 25 % of meals served. Irrespective of pre-fracture functional status, patients with DI <= 25 % had significantly lower Barthel index scores at all times after surgery (all P50 % more often had regained their pre-fracture mobility level than those with DI <= 25 % at discharge (>50 %: 36 %; >25-50 %: 10 %; <= 25 %: 0 %; P= 0·001) and 6 months after discharge (88; 87; 68 %; P= 0·087) and had significantly less complications (median 2 (25th-75th percentile 1-3); 3 (25th-75th percentile 2-4); 3 (25th-75th percentile 3-4); P= 0·012). To conclude, geriatric HF patients had very low postoperative voluntary DI and thus need specific nutritional interventions to achieve adequate DI to support functional and clinical recovery.
EVALuna2:5509

Low postoperative Food Intake in the Hospital is linked to geriatric Hip Fracture- Pateients with Complications and Loss of Function - Goisser, Sabine; Schrader, Eva; Singler, Katrin; Sieber, Cornel; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2014)

Malnutrition According to Mini Nutritional Assessment Is Associated With Severe Functional Impairment in Geriatric Patients Before and up to 6 Months After Hip Fracture - Goisser, Sabine; Schrader, Eva; Singler, Katrin; Bertsch, Thomas; Gefeller, Olaf; Biber, Roland; Bail, Hermann Josef; Sieber, Cornel; Volkert, Dorothee (Journal of the American Medical Directors Association, 2015)
Hip fractures (HFs) in old age frequently cause severe functional impairment and deteriorating autonomy in everyday life. Many older patients with HFs are malnourished or at risk of malnutrition. In this study, we examined the relationship between nutritional status of geriatric patients before HF and their functional and clinical course up to 6 months after hospital discharge.Observational study with follow-up after 6 months.Four wards of the department of trauma and orthopedic surgery of a large urban maximum care hospital (Klinikum Nürnberg, Nuremberg, Germany).Geriatric patients aged >=75 years with surgically repaired proximal femoral fracture.Prefracture nutritional status was determined by Mini Nutritional Assessment (MNA). Comorbidities and complications during hospital stay were obtained from medical documentation. Functional status before HF, postoperatively, at hospital discharge, and 6 months later was assessed by Barthel Index for activities of daily living (ADL) and patients' mobility level and related to MNA categories. Associations were evaluated using ?(2), Fisher exact, Kruskal-Wallis, Mann-Whitney-U, Jonckheere-Terpstra, and Cochrane-Armitage tests as appropriate, as well as analysis of covariance with repeated measures.Of 97 included patients, 17% were malnourished and 38% at risk of malnutrition before HF. Participants with (risk of) malnutrition were equally mobile but more dependent in ADL prior to HF than well-nourished patients (P < .001). Independent of nutritional status, after 6 months 68% of participants had not regained their prefracture level of independence in ADL. According to analysis of covariance, the ADL development over time until follow-up 6 months after hospital discharge did not depend on nutritional status. However, at follow-up malnourished patients more often suffered from remaining losses in ADL >=25% of initial Barthel Index points (P = .033) and less often had regained their prefracture mobility level (P = .020) than well-nourished patients. Clinical course did not differ significantly between the groups with different nutritional status.In this study with geriatric HF patients from all functional and cognitive levels, worse prefracture nutritional status was associated with worse functional status and more frequent remaining functional loss, whereas the trajectory of ADL recovery and clinical course did not differ significantly. Further studies with sufficient statistical power are needed to substantiate these inconclusive results. In order to clarify the association of nutritional status with functional and clinical course in geriatric patients after HF, they should preferably focus on the role of nutritional management during the hospital stay.
EVALuna2:5524

Malnutrition According to Mini Nutritional Assessment Is Associated With Severe Functional Impairment in Geriatric Patients Before and up to 6 Months After Hip Fracture - Goisser, Sabine; Schrader, Eva; Singler, Katrin; Bertsch, Thomas; Gefeller, Olaf; Biber, Roland; Bail, Hermann Josef; Sieber, Cornel; Volkert, Dorothee (Journal of the American Medical Directors Association, 2015)
Objectives: Hip fractures (HFs) in old age frequently cause severe functional impairment and deteriorating autonomy in everyday life. Many older patients with HFs are malnourished or at risk of malnutrition. In this study, we examined the relationship between nutritional status of geriatric patients before HF and their functional and clinical course up to 6 months after hospital discharge.Design: Observational study with follow-up after 6 months.Setting: Four wards of the department of trauma and orthopedic surgery of a large urban maximum care hospital (Klinikum Nurnberg, Nuremberg, Germany).Participants: Geriatric patients aged >= 75 years with surgically repaired proximal femoral fracture.Measurements: Prefracture nutritional status was determined by Mini Nutritional Assessment (MNA). Comorbidities and complications during hospital stay were obtained from medical documentation. Functional status before HF, postoperatively, at hospital discharge, and 6 months later was assessed by Barthel Index for activities of daily living (ADL) and patients' mobility level and related to MNA categories. Associations were evaluated using chi(2), Fisher exact, Kruskal-Wallis, Mann-Whitney-U, Jonckheere-Terpstra, and Cochrane-Armitage tests as appropriate, as well as analysis of covariance with repeated measures.Results: Of 97 included patients, 17% were malnourished and 38% at risk of malnutrition before HF. Participants with (risk of) malnutrition were equally mobile but more dependent in ADL prior to HF than well-nourished patients (P < .001). Independent of nutritional status, after 6 months 68% of participants had not regained their prefracture level of independence in ADL. According to analysis of covariance, the ADL development over time until follow-up 6 months after hospital discharge did not depend on nutritional status. However, at follow-up malnourished patients more often suffered from remaining losses in ADL >= 25% of initial Barthel Index points (P = .033) and less often had regained their prefracture mobility level (P = .020) than well-nourished patients. Clinical course did not differ significantly between the groups with different nutritional status.Conclusions: In this study with geriatric HF patients from all functional and cognitive levels, worse prefracture nutritional status was associated with worse functional status and more frequent remaining functional loss, whereas the trajectory of ADL recovery and clinical course did not differ significantly. Further studies with sufficient statistical power are needed to substantiate these inconclusive results. In order to clarify the association of nutritional status with functional and clinical course in geriatric patients after HF, they should preferably focus on the role of nutritional management during the hospital stay. (C) 2015 AMDA - The Society for Post-Acute and Long-Term Care Medicine.
Keywords: Malnutrition; hip fracture; geriatric patients; hospital; functional recovery; Mini Nutritional Assessment (MNA)

Malnutrition and related risk factors in older adults from different health-care settings: An enable study - Kiesswetter, Eva; Colombo, Miriam G.; Meisinger, Christa; Peters, Annette; Thorand, Barbara; Holle, Rolf; Ladwig, Karl Heinz; Schulz, Holger; Grill, Eva; Diekmann, Rebecca; Schrader, Eva; Stehle, Peter; et al. (Public Health Nutrition, 2019)
Objective:The origin of malnutrition in older age is multifactorial and risk factors may vary according to health and living situation. The present study aimed to identify setting-specific risk profiles of malnutrition in older adults and to investigate the association of the number of individual risk factors with malnutrition.Design:Data of four cross-sectional studies were harmonized and uniformly analysed. Malnutrition was defined as BMI < 20 kg/m2 and/or weight loss of >3 kg in the previous 3-6 months. Associations between factors of six domains (demographics, health, mental function, physical function, dietary intake-related problems, dietary behaviour), the number of individual risk factors and malnutrition were analysed using logistic regression.Setting:Community (CD), geriatric day hospital (GDH), home care (HC), nursing home (NH).Participants:CD older adults (n 1073), GDH patients (n 180), HC receivers (n 335) and NH residents (n 197), all ≥65 years.Results:Malnutrition prevalence was lower in CD (11 %) than in the other settings (16-19 %). In the CD sample, poor appetite, difficulties with eating, respiratory and gastrointestinal diseases were associated with malnutrition; in GDH patients, poor appetite and respiratory diseases; in HC receivers, younger age, poor appetite and nausea; and in NH residents, older age and mobility limitations. In all settings the likelihood of malnutrition increased with the number of potential individual risk factors.Conclusions:The study indicates a varying relevance of certain risk factors of malnutrition in different settings. However, the relationship of the number of individual risk factors with malnutrition in all settings implies comprehensive approaches to identify persons at risk of malnutrition early.
CRIS-Team Scopus Importer:2019-10-15
Keywords: Malnutrition; Older people; Risk factor; Setting

Malnutrition in geriatric Hip Fracture- Patients associated with functional Limitations - Goisser, Sabine; Schrader, Eva; Purucker, Katja; Singler, Katrin; Biber, R.; Bail, H. J.; Sieber, Cornel; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2013)

Nutritional and functional status in geriatric day hospital patients-MNA short form versus full MNA - Schrader, Eva; Grosch, Ella; Bertsch, T.; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2016)
The aims of this study were to determine the prevalence of malnutrition in patients of a geriatric day hospital using the Mini Nutritional Assessment short form (MNA-SF) and the full MNA, to compare both tools, and to examine the relationship between nutritional and functional status.Cross-sectional study.Geriatric day hospital.190 patients (72.1% female, median 80 years) aged 65 years or older.In consecutively admitted geriatric day hospital patients nutritional status was assessed by MNA-SF and full MNA, and agreement between both tools calculated by Cohen's kappa. Basic activities of daily living (ADL), instrumental activities of daily living (IADL) and short physical performance battery (SPPB) were determined and related to MNA categories (Chi(2)-test, Mann-Whitney-U-test).36.3 % and 44.7% of the patients were at risk of malnutrition, 8.9 % and 5.8 % were malnourished according to MNA-SF and full MNA, respectively. Agreement between both MNA forms was moderate (?=0.531). No significant associations between MNA-SF and ADL, IADL and SPPB, and between full MNA and SPPB were observed. According to full MNA, the proportion of patients with limitations in ADL and IADL significantly increased with declining nutritional status (ADL: 2.1 vs. 8.2 vs. 18.2 %, p=0.044; IADL: 25.5 vs. 47.1 vs. 54.5 %, p=0.005) with a simultaneous decrease of the proportion of patients without limitations. Well-nourished patients reached significantly higher ADL scores than patients at risk of malnutrition (95 (-100) vs. 95 (85- 100), p=0.005) and significantly higher IADL scores than patients at risk or malnourished (8 (6-8) vs. 7 (5-8) vs. 6 (4-8), p=0.004).The high prevalence of risk of malnutrition and the observed association between functional status and nutritional status according to full MNA call for routine nutritional screening using this tool in geriatric day hospital patients.
Keywords: Nutritional status; mini nutritional assessment; functional status; geriatric day hospital patients

Nutritional status according to mini nutritional assessment is related to functional status in geriatric patients–independent of health status - Schrader, Eva; Baumgartel, C.; Gueldenzoph, H.; Stehle, P.; Uter, Wolfgang; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2014)
The aim of this study was to investigate the relationship between nutritional and functional status in acute geriatric patients including mobility and considering health status.Cross-sectional study.Hospital.205 geriatric patients (median age 82.0 (IQR: 80-86) years, 69.3% women).Nutritional status was determined by Mini Nutritional Assessment (MNA) and patients were categorized as well-nourished (>= 24 points), at risk of malnutrition (17-23.5 points) or as malnourished (< 17 points). Functional status was determined by Barthel Index (BI) and Timed 'Up and Go' Test (TUG) and related to MNA categories. Using binary multiple logistic regression the impact of nutritional status on functional status was examined, adjusted for health status.60.3% of the patients were at risk of malnutrition and 29.8% were malnourished. Ability to perform basic activities of daily living (ADL) decreased with declining nutritional status. The proportion of patients unable to perform the TUG increased with worsening of nutritional status (45.0% vs. 50.4% vs. 77.0%, p<0.01). After adjusting for age, gender, number of diagnoses, disease severity and cognitive function, a higher MNA score significantly lowered the risk of being dependent in ADL (OR 0.85, 95 % CI 0.77-0.94) and inability to perform the TUG (OR 0.90, 95 % CI 0.82-0.99).Nutritional status according to MNA was related to ADL as well as to mobility in acute geriatric patients. This association remained after adjusting for health status.
EVALuna2:5451

NUTRITIONAL STATUS ACCORDING TO MINI NUTRITIONAL ASSESSMENT IS RELATED TO FUNCTIONAL STATUS IN GERIATRIC PATIENTS-INDEPENDENT OF HEALTH STATUS - Schrader, Eva; Baumgartel, C.; Gueldenzoph, H.; Stehle, P.; Uter, Wolfgang; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2014)
Objectives: the aim of this study was to investigate the relationship between nutritional and functional status in acute geriatric patients including mobility and considering health status. Design: cross-sectional study. Setting: hospital. Participants: 205 geriatric patients (median age 82.0 (IQR: 80-86) years, 69.3% women). Measurements: nutritional status was determined by mini nutritional assessment (MNA) and patients were categorized as well-nourished (>= 24 points), at risk of malnutrition (17-23.5 points) or as malnourished (< 17 points). Functional status was determined by Barthel index (BI) and Timed. 'Up and Go' Test (TUG) and related to MNA categories. using binary multiple logistic regression the impact of nutritional status on functional status was examined, adjusted for health status. Results: 60.3 % of the patients were at risk of malnutrition and 29.8 % were malnourished. ability to perform basic activities of daily living (ADL) decreased with declining nutritional status. the proportion of patients unable to perform the tug increased with worsening of nutritional status (45.0 % vs. 50.4 % vs. 77.0 %, p<0.01). after adjusting for age, gender, number of diagnoses, disease severity and cognitive function, a higher MNA score significantly lowered the risk of being dependent in ADL (OR 0.85, 95 % CI 0.77-0.94) and inability to perform the tug (OR 0.90, 95 % CI 0.82-0.99). Conclusion: nutritional status according to MNA was related to ADL as well as to mobility in acute geriatric patients. this association remained after adjusting for health status.
Keywords: Nutritional status; MNA; functional status; mobility; hospitalized geriatric patients

Pain & Illness substantially endanger the Nutritional Status of Patients in a geriatric Day Hospital - Schrader, Eva; Ehrhardt, Sabine; Sieber, Cornel; Volkert, Dorothee (Internist, 2013)

Varying Associations Between Body Mass Index and Physical and Cognitive Function in Three Samples of Older Adults Living in Different Settings - Kiesswetter, Eva; Schrader, Eva; Diekmann, Rebecca; Sieber, Cornel; Volkert, Dorothee (Journals of Gerontology Series A-Biological Sciences and Medical Sciences, 2015)
The study investigates variations in the associations between body mass index (BMI) and (a) physical and (b) cognitive function across three samples of older adults living in different settings, and moreover determines if the association between BMI and physical function is confounded by cognitive abilities.One hundred ninety-five patients of a geriatric day hospital, 322 persons receiving home care (HC), and 183 nursing home (NH) residents were examined regarding BMI, cognitive (Mini-Mental State Examination), and physical function (Barthel Index for activities of daily living). Differences in Mini-Mental State Examination and activities of daily living scores between BMI groups (<22, 22-<25, 25-<30, 30-<35, >=35kg/m(2)) were tested by analysis of covariance considering relevant confounders.Activities of daily living and Mini-Mental State Examination impairments increased from the geriatric day hospital over the HC to the NH sample, whereas prevalence rates of obesity and severe obesity (35%, 33%, 25%) decreased. In geriatric day hospital patients cognitive and physical function did not differ between BMI groups. In the HC and NH samples, cognitive abilities were highest in obese and severely obese subjects. Unadjusted mean activities of daily living scores differed between BMI groups in HC receivers (51.6±32.2, 61.8±26.1, 67.5±28.3, 72.0±23.4, 66.2±24.2, p = .002) and NH residents (35.6±28.6, 48.1±25.7, 39.9±28.7, 50.8±24.0, 57.1±28.2, p = .029). In both samples significance was lost after adjustment indicating cognitive function as dominant confounder.In older adults the associations between BMI and physical and cognitive function were dependent on the health and care status corresponding to the setting. In the HC and the NH samples, cognitive status, as measured by the Mini-Mental State Examination, emerged as an important confounder within the association between BMI and physical function.
EVALuna2:10586